Corruption in the systmen an the sick city in the black novel PASADO PERFECTO by Leonardo Padura - Arley Fonseca, Mauricio (2018)
Citizens are a symptom of their political system, its surface expression, according to what underlies the space of power. In Pasado perfecto corruption and sickness signs are disseminated, which will be studied using the word as a resource. The plot starts with an inquiry into the disappearance of Morin (an important Cuban businessman); his wife, Tamara Valdemira, who reports it, is stomatologist specializing in medical signs that occur in the mouth. Which sicknesses could emerge from a mouth analysis? Utterances and what is left unspoken will be references for obtaining answers about the corruption that invades the social system and the pathological condition the subjects from this system suffer. This disappearance broaches a historical precedent in politics: the schism in the Cuban community after the fall of the Berlin Wall and the disappearance of the father (the Soviet Union), leading to the emergence of new orders of power relations. The analysis will stem from psychoanalytic and semiotic theories, in order to extract the latent from the act of crime, where it will be demonstrated that the social system, due to the order and its power groups, is damaged and corrupts any subject attached to its structure. A brief version of this work was presented in the Research Workshop of the Research Center on Cultural Diversity andRegional Studies.